Sensationalism in Reporting Conflict: The Case of Yazidi Women’s Portrayal in the Daily Mail Online After 2014 - Arazoo Rasool Ahmed; Manvender Kaur A/P Sarjit Singh (QALAAI ZANIST SCIENTIFIC JOURNAL, 2025)
This research is an attempt to fathom the sensationalist ways in which the Daily Mail Online framed the narratives of the Yazidi women during the period after the atrocities carried out by the so-called Islamic State in 2014. This paper identifies the predominating victim-based narrative, interwoven with themes of resilience and post-conflict challenges, predominantly emphasizing the motif of sexual violence in eighty articles from the period between 2014 and 2020 within the postcolonial feminist theory framework. The research is enabled by using NVivo 12 in thematic analysis applied through Braun and Clarke’s (2006) six-step method. The results show how these portrayals build up a victimized identity for Yazidi women, but at the same time, elements of resilience are depicted. This paper provides substantial contributions to the already existing literature on media representation of gender in conflict areas, underscoring the necessity of ethical journalism and reporting sensitive to gender. These understandings underline the critical role that journalism can play in the empowerment and support of women affected by the war.